Efektivitas Interprofessional Education (IPE) Terhadap Kompetensi Antar Profesi Kesehatan - Amaze Morato; Ni Luh Putu Eka Diarthini; Desak Ketut Indrasari Utami (Husada Mahakam, 2021)
Background: Interprofessional Education (IPE) is a learning process between various students or health workers with various educational backgrounds who interact and collaborate to produce and provide promotive, preventive, curative and rehabilitative health services. Objective: The purpose of this study is to find out how effective interprofessional education is towards competantion between health profession. Method: The research method in this study is a literature study article or narrative review in the form of a study of several research journals related to the effectiveness of interprofessional education on competention between health profession obtained through Google Scholar, PubMed, and Science Direct. Results: The benefits of IPE activities are students can learn to collaborate and function in a team and bring this knowledge, skills and attitudes into future practice through enhancing several aspects such as communicating, collaborating, determining the roles and responsibilities of each profession, conflict management, decision making, sharing knowledge and skills and finally mutual respect between friends. Conclusion: Based on the cited literature review, it can be concluded that interprofessional education (IPE) on collaboration between health services can create professional health workers, can collaborate and collaborate with other professions, understand and respect inter-profession of health services. Keywords: Interprofessional Education (IPE), Health Profission